2007
DOI: 10.1002/elps.200600759
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids: Aspects of impurity profiling by means of CE

Abstract: Quality control of active pharmaceutical ingredients (API) is commonly performed by means of HPLC. However, CE offers a suitable alternative, especially for the analysis of easily chargeable substances, i.e., amino acids. The article reviews, on the one hand, CE methods developed for impurity profiling of synthesized amino acid analogs. However, nowadays, production of amino acids/peptides is dominated by fermentation. Therefore, on the other hand, CE methods for the analysis of amino acids and small peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In addition the levels of examined aromatic amino acids in whole blood hydrolysates obtained in the present study are significantly higher from reported plasma values [12][13][14] confirming the fact that their intracellular levels are above extracellular ones. Recently, the others [23] have also reported CE as a suitable tool for the quality control of amino acids and glutathione, although they analyzed samples after derivatization and testing the method for analysis in the pharmaceutical field. The method obtained in the present study permits simultaneous measuring of GSH and GSSG and some amino acids by CE in biological fluids.…”
Section: Testing the Methods On Blood Sample Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…In addition the levels of examined aromatic amino acids in whole blood hydrolysates obtained in the present study are significantly higher from reported plasma values [12][13][14] confirming the fact that their intracellular levels are above extracellular ones. Recently, the others [23] have also reported CE as a suitable tool for the quality control of amino acids and glutathione, although they analyzed samples after derivatization and testing the method for analysis in the pharmaceutical field. The method obtained in the present study permits simultaneous measuring of GSH and GSSG and some amino acids by CE in biological fluids.…”
Section: Testing the Methods On Blood Sample Analysismentioning
confidence: 98%
“…Also during the last decade CE has become an important tool for the analysis of a wide variety of biological molecules including amino acids and peptides [17,19,20]. Since free amino acids generally possess very limited chromophores derivatization procedures prior CE are usually used [22,23], but there are also attempts to analyze amino acids directly, without their derivatization employing measurement of indirect absorbance or use other detection capabilities [17,20]. Considering possibility of an in vitro thiols/disulfides interconversion during derivatization procedure it seems more convenient to analyze their native forms present in physiological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Kopec and Holzgrabe applied three methods for amino acids impurity detection, and these methods include European Pharmacopoeia monograph for glutathione, derivatization with 9‐fluorenylmethyl chloroformate for amino acid samples, and 3‐(4‐carboxybenzoyl)‐quinoline‐2‐carboxaldehyde for amino acids and small peptides. Their results indicated that all of these methods were suitable for impurity profiling of amino acids products produced by fermentative pathways .…”
Section: Analyte Classes Important In Bioprocess Analysismentioning
confidence: 99%
“…fluorescein isothiocyanate (FITC) [27], fluorenylmethyloxycarbonyl chloride (FMOCCl) [28], 3-(4-carboxybenzoyl)quinoline-2-carboxaldehyde (CBQCA) [29,30], and ortho-phthalaldehyde (OPA) [31]. OPA is a proven reagent which allows for a fast derivatization of AAs.…”
Section: Introductionmentioning
confidence: 99%